ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI BEHAVIORAL INTENTION DAN USE BEHAVIOR PADA APLIKASI TIKTOK SHOP (Lembaga Penerbitan Unversitas Esa Unggul, 2022)
This study aims to determine the direct effect of performance expectancy, effort expectancy, and social influence on behavior intention and use behavior, and the indirect effect of performance expectancy, effort expectancy, and social influence on use behavior through the behavior intention of users of the TikTok Shop application. Respondents in this study are all people who have shopped through the TikTok Shop application and are domiciled in the JABODETABEK area. The sampling technique used was purposive sampling with a total of 160 respondents and the data analysis used was SEM-PLS. The results showed that performance expectancy, effort expectancy, and social influence had a positive influence on behavior intention. Performance Expectancy, effort expectancy, and behavior intention have a positive influence on use behavior. However, social influence has no effect on use behavior. Social influence has a positive influence on use behavior through behavior intention, but Performance expectancy and effort expectancy has no effect on use behavior through behavior intention.